1996
DOI: 10.1159/000244361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preweaning Environmental Stimulation on Neuronal and Behavioral Impairment Produced by Undernutrition

Abstract: The present study investigates the effects of sensorimotor stimulation on the basal dendrogenesis of superficial cerebrocortical neurons and the accomplishment in the associated exploratory behavior in rats simultaneously exposed to nutritional deprivation. Sprague-Dawley albino rats were submitted to nutritional-environmental influences from birth to the 21 st postnatal day. Exploratory behavior was assessed by the evaluation of locomotor activity in the open-field apparatus. In order to evaluate changes in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…At P82 all animals were examined for locomotor activity in response to novelty in the open-field apparatus as previously described [21] . Briefly, each rat was placed in the center of 80 !…”
Section: Behavioral Analysismentioning
confidence: 99%
“…At P82 all animals were examined for locomotor activity in response to novelty in the open-field apparatus as previously described [21] . Briefly, each rat was placed in the center of 80 !…”
Section: Behavioral Analysismentioning
confidence: 99%
“…At this time the mother was taken away, and within the litter, males and females were separated and reared apart in similar cages until the adult period. We chose to place the animals in the enriched cages from birth because it has been demonstrated that preweaning environmental conditions influence both behavior (Labarba, Fernandez, White, & Stewart, 1974;Labarba & Stewart, 1976;Pascual, Hervias, & Figueroa, 1996) and development of the central nervous system (Fulker & Rick, 1973;Pascual, Hervias, Toha, Valero, & Figueroa, 1998;Sanchez, Aguado, Sanchez-Toscano, & Saphier, 1995;Venable, Fernandez, Diaz, & Pinto-Hamuy, 1989) and, interestingly, that in rats, preweaning was more efficient than postweaning enrichment in their learning capabilities (Venable et al, 1988).…”
Section: Rearing Environmentsmentioning
confidence: 99%
“…These data indicate negative effects of sensory activation deficiency on malnourished brain. On the other hand, malnourished organisms under nutritional therapy recover better when environmental stimulation is added to that therapy (Celedon and De Andraca, 1979; Grantham‐McGregor et al, 1991), and the same seems to be true in laboratory animals (Lima et al, 1999; Pascual et al, 1996). The presumption that changes in CSD features, under the present experimental conditions, can reflect plastic modifications of neural function (Cheetham et al, 2007) seems to us an interesting issue to be further addressed, concerning the susceptibility of the human brain to highly disabling, development‐dependent and energy‐consuming diseases, such as epilepsy and migraine (Rogawski, 2008; Welch, 2005) and brain ischemia (Dohmen et al, 2008; Fabricius et al, 2008).…”
Section: Discussionmentioning
confidence: 99%